The Return Back to Typical Practice from the “Battle Plan” of the Coronavirus Disease 2019 (COVID-19) Pandemic: A Comparative Study - Pressman, Elliot (World Neurosurg, 2020)
BACKGROUND: Every aspect of the medical field has been heavily affected by the coronavirus disease 2019 (COVID-19) pandemic, and neurosurgical services are no exception. Several departments have reported their experiences and protocols to provide insights for others impacted. The goals of this study are to report the load and variety of neurosurgical cases and clinic visits after discontinuing the COVID-19 Battle Plan at an academic tertiary care referral center to provide insights for other departments going through the same transition. METHODS: The clinical data of all patients who underwent a neurosurgical intervention between May 4, 2020, and June 4, 2020 were obtained from a prospectively maintained database. Data of the control group were retrospectively collected from the medical records to compare the types of surgeries/interventions and clinic visits performed by the same neurosurgical service before the COVID-19 pandemic started. RESULTS: One hundred sixty-one patients underwent neurosurgical interventions, and seven-hundred one patients were seen in clinic appointments, in the 4-week period following easing back from our COVID-19 “Battle Plan.” Discontinuing the “Battle Plan” resulted in increases in case load to above-average practice after a week but a continued decrease in clinic appointments throughout the 4 weeks compared with average practice. CONCLUSIONS: As policy-shaping crises like pandemics abate, easing back to “typical” practice can be completed effectively by appropriately allocating resources. This can be accomplished by anticipating increases in neurosurgical volume, specifically in the functional/epilepsy and brain tumor subspecialties, as well as continued decreases in neurosurgical clinic volume, specifically in elective spine.